Excellent energy storage density and efficiency in blend polymer-based composites by design of core-shell structured inorganic fibers and sandwich structured films. (15th November 2019) - Cui, Yang; Zhang, Tiandong; Feng, Yu; Zhang, Changhai; Chi, Qingguo; Zhang, Yongquan; Chen, Qingguo; Wang, Xuan; Lei, Qingquan
Abstract: In this study, the ferroelectric polyvinylidene fluoride (PVDF) blended with linear dielectric polymethyl methacrylate (PMMA) is chosen as polymer matrix (named as PMMA/PVDF). The effect of PMMA content and differently structured fillers on the microstructures and electrical properties of PMMA/PVDF-based composites have been investigated. The inorganic 0.5Ba(Zr0.2 Ti0.8 )O3 - 0.5(Ba0.7 Ca0.3 )TiO3 fibers (abbreviated as BCZT), BCZT embedded with Ag particles (BCZT+Ag), and core-shell structured BCZT+Ag@Al2 O3 fibers as fillers were designed and prepared by electrospinning technology. As the insulating Al2 O3 shell layer could relieve the dielectric difference between the BCZT and polymer matrix and confine the mobility of carriers provided by Ag, the energy storage density and efficiency are 4.02 J/cm 3 and 78.0% for the 3 vol% BCZT+Ag@Al2 O3 /40% PMMA/PVDF composites at an electric field of 320 kV/mm. To further improve the energy storage properties of the single-layered composites, the sandwich-structured composite films have been designed to improve the breakdown strength. The results show that the energy storage density and efficiency of sandwich-structured composite film with 40 wt% PMMA/PVDF as outer layer and 3 vol% BCZT+Ag@Al2 O3 /40% PMMA/PVDF as inter layer are 9.6 J/cm 3 and 69.8%, respectively, at an electric field of 400 kV/mm. This work presents an effective way to improve the energy storage properties of inorganic/polymer composites. Graphical abstract: Image 1 Highlights: The ferroelectric PVDF blended with linear dielectric polymethyl methacrylate (PMMA) is chosen as the polymer matrix. The inorganic composited fillers BCZT+Ag@Al2 O3 with multiple interfacial structure have been designed. The sandwich structured composite films have been designed for further increasing the energy storage density.